Kedudukan dan Perlindungan Hukum Kreditor Separatis Terhadap Harta Debitor Pailit Berdasarkan Pasal 55 Ayat (1) Undang-Undang Kepailitan dan Penundaan Kewajiban Pembayaran Utang - Fadhli, Muhammad; Arrisman, Arrisman; Rumainur, Rumainur (Dinasti Review Publisher, 2024)
Separatist creditors are among the parties with interests in the assets of a bankrupt debtor. Article 55 paragraph (1) of the Bankruptcy and Debt Payment Delay Law specifically grants separatist creditors the right to execute assets that serve as collateral as if bankruptcy had not occurred. This article also places separatist creditors in a higher position compared to other creditors.